KAJIAN KONSENTRASI COCOA POWDER PADA MINUMAN COKELAT TERHADAP KADAR GLUKOSA DARAH - Agus Sudrajat; Ai Susanti; Sani Fitriyani (POLITEKNIK PIKSI GANESHA, 2020)
One type of disease due to the pattern of wrong pattern of food consumption is Diabetes Mellitus (DM). Diabetes mellitus is characterized by an increase in blood glucose levels (hyperglycemia). The treatment of this disease requires a lot of cost and a long peroid of time, this experiment were intended to conduct research on cocoa powder which in the previous research reveals that cocoa powder contains high levels of flavonoids which has the potential as functional food to control or even lowered blood glucose levels. This research using experimental method of pretest and post test by using male wistar strain rats as the animal of experiment, with the total number of 35 rat. There were 5 group : the negative control which fed by standar food animal and drink, positive control was given food and drink and induced with alloxan, 4 treatment groups with chocolate beverage with cocoa powder concentration of 1%, 2% and 3% which was previously induced by alloxan. The treatment was performed in 14 days and on the 14th day, the blood glucose level was examined. Data were analyzed using Anova test, Tukey test and Paired T Test. The results showed that there was a decrease of the glucose level in treatment group which is treated by chocolate drink with 1%, 2% and 3% of cocoa powder concentration, with significant value in all statistical test with p value <0,05. The conclusion of this research was that the concentration of cocoa powder 1 until 3% in chocolate beverage has a functional characteristic to lowered blood glucose level.